Antibody-Dependent Cellular Inhibition Is Associated With Reduced Risk Against Febrile Malaria in a Longitudinal Cohort Study Involving Ghanaian Children. (10th April 2015) - Tiendrebeogo, Regis W.; Adu, Bright; Singh, Susheel K.; Dziegiel, Morten H.; Nébié, Issa; Sirima, Sodiomon B.; Christiansen, Michael; Dodoo, Daniel; Theisen, Michael
Abstract: The antibody-dependent respiratory burst and opsonic phagocytosis assays have been associated with protection against malaria; however, other mechanisms may also be involved. The antibody-dependent cellular inhibition (ADCI) assay is yet to be correlated with protection in longitudinal cohort studies (LCS). We investigated the relationship between ADCI activity of immunoglobulin G before malaria season and risk of malaria in a LCS involving Ghanaian children. High ADCI activity was significantly associated with reduced risk against malaria. Findings here suggest a potential usefulness of the ADCI assay as a correlate of protection to guide malaria vaccine studies.